Backup capacity coordination with renewable energy certificates in a regional electricity market. (3rd August 2018) - Zhou, Yingjue; Liu, Tieming; Zhao, Chaoyue
ABSTRACT: This article studies a coordination mechanism between a renewable energy supplier and a conventional supplier in a regional electricity market. The intermittent nature of the renewable supplier results in random power shortages. Though the renewable supplier can buy backup power from a conventional supplier who prepares backup capacity to cover the shortage, there is no commitment that enough backup capacity will be prepared without any incentives to the conventional supplier. We design a coordination mechanism where the renewable supplier offers the conventional supplier Renewable Energy Certificates (RECs) proportional to the backup capacity committed. We prove that this mechanism coordinates the conventional supplier's decision on backup capacity and can arbitrarily split the system profit between the two suppliers. Our analytical results show that when the shortage cost increases, the backup capacity increases, the REC offering rate increases, the total profit decreases, and the renewable supplier's profit decreases but the conventional supplier's profit increases. We also show analytically that the social welfare under this mechanism is higher than in the decentralized case unless the regional environment is extremely sensitive to conventional power's carbon footprint, and the benefit of buffering power shortage cannot compensate for the damage to the environment.